The Impact of Approved Accounting Standard AASB 1024 â€œConsolidated Accountsâ€ on the Information Included in Consolidated Financial Statements - Pramuka, Bambang Agus (Accounting Department,, 1995)
TheÂ intentÂ ofÂ consolidatedÂ financialÂ statementsÂ isÂ toÂ provide meaningful, relevant,Â useful,Â and reliableÂ information about the operations of aÂ groupÂ of companies.Â InÂ complianceÂ withÂ AASBÂ 1024Â â€™Consolidated Accountsâ€™,Â andÂ AASÂ 24Â ConsolidatedÂ FinancialÂ Reportsâ€™, aÂ parentÂ entity nowÂ hasÂ toÂ includeÂ inÂ itsÂ consolidatedÂ financialÂ statementsÂ allÂ controlled entities,Â regardless of theirÂ legalÂ formÂ or theÂ ownershipÂ interestÂ held.Â The newÂ StandardÂ alsoÂ providesÂ aÂ newÂ styleÂ ofÂ consolidatedÂ financial statements format, which requires an increased disclosure of outside equity interest (OEI,Â formerly minorityÂ interest),Â especiallyÂ inÂ theÂ BalanceÂ Sheet. The purpose of this study is to determine the impact of AASB 1024 on the consolidated financial statements of effected companies.Â ExaminationÂ of theÂ financialÂ statementsÂ of 52Â companiesÂ reveals that:Â (1) theÂ adoptionÂ of AASBÂ 1024 (and AAS 24) did significantly alter the structure and Â format of the basicÂ financialÂ statements,Â especially theÂ BalanceÂ SheetÂ in terms of disclosing the OEI; and (2) the adoption of AASBÂ 1024 (and AAS 24) had no significant impact on the consolidated financial figures.